Plan de seguridad y salud ocupacional para la minimización de riesgos físicos en la empresa camaronera "Fercho" - Iturralde Zapata, Cristhian Israel (2017)
The research consisted in designing an occupational safety and health plan for the shrimp farmer “Fercho”, Canton Chone, San Antonio. The company has 12 activities such as: pool preparation, reception source and larvae, seed density, pre-fattening, population sampling, shrimp weight, etc. The workers of the plant answered in the survey, they do not know about the risks they are exposed to do not have a work program, among others. Vibration and noise monitoring are within the permissible limits of the applicable legislation (environmental and labor management law) except for noise in the pool filling area that exceeds the decibels contemplated in the legislation, due to the capacity of the bombs. The triple criterion matrix, together with the William Fine method of 1971, estimated that the number of risks present is modest in nature (16) with no significant and intolerant risk to the plant. The methodology of William Fine considered that the physical risks have a degree of danger and repercussion of low level. These estimated and evaluated risks contributed to the development of a plan to minimize and / or prevent major physical risks (noise and vibration), as a proposal for the continuous improvement of the same.